Prevalência e fatores associados à infecção pelo HIV em gestantes e parturientes - Porto, Maria Laura de Almeida (2017)
Introduction: The increase in HIV-positive heterosexuals and the consequent contamination of women of reproductive age leads to a higher occurrence of vertical transmission. Therefore, it is relevant to assess the risk factors associated with HIV infection. Objectives: To make an original article to evaluate the prevalence in the rapid test for HIV in pregnant women hospitalized for obstetric emergencies (births and abortions). Make an original article to evaluate the prevalence of HIV infection in low- and high-risk prenatal care and to define the factors associated with HIV infection in pregnant women and parturients in a maternity hospital in Goiânia. Methodology: Cross-sectional study, case-control. The case group consisted of 15 HIV-positive patients who agreed to participate in the study, for which the epidemiological profile was drawn. The control group consists of a sample of 60 non-HIV patients, for whom the same profile of the case group was drawn. Patients attended during the prenatal care and in the emergency of the Dona Iris Hospital and Maternity Unit in Goiânia-Goiás, between 08/01/2015 and 03/30/2017 were recruited for the interview; and prevalences were assessed. Results: The sample N consisted of 10,822 patients, 617 of low risk prenatal care, 754 of high risk and 9,451 of urgency. Of these, 25 had positive serology for HIV. The overall prevalence of HIV-positive patients was 0.23% and they had a mean age of 25 to 29 years, most of them living in a stable union, with a previous number of partners > 10, schooling until high school, evangelicals and employed in the interview period, with family income between 1 and 2 minimum wages. Conclusion: The article 1 concludes: The prevalence of HIV-positive pregnant women admitted to the obstetric emergency in which the rapid test was performed was 0.11%. We conclude in article 2: The seroprevalence of HIV infection in low prenatal care was 0.32%. Seroprevalence in high-risk prenatal care was 1.72%. The epidemiological profile was similar in both groups and among the factors associated with HIV infection, two were the significant variables when compared to the non-infected group: mean age of the patients (25 to 29 years) and number of partners previous to the current gestation (> 10), which were higher in the group of people living with HIV.